Stakeholders’ views and experiences on implementing new diagnostics in primary care to support management of community-acquired acute respiratory tract infections: a qualitative study - Hoste, ME; Colman, E; Wanat, M; Hayward, G; Tissier, J-L; Postma, M; Goossens, H; Anthierens, S; Tonkin-Crine, S (Frontiers Media, 2023)
Background: The majority of antibiotics are prescribed in primary care for respiratory tract infections. Point-of-care tests (POCTs) for the management of community-acquired acute respiratory tract infections (CA-ARTI) have been developed to help optimize antibiotic prescribing. While some countries in Europe have adopted these tests in primary care settings, most have not. Stakeholders, such as policy-makers, regulators, the diagnostic industry, and scientific associations, have roles in the implementation of new diagnostics in primary care. The aim of this study is to explore these stakeholders’ views and experiences, and identify areas of unmet need relating to POCT implementation.